Microgrid capability diagram: A tool for optimal grid-tied operation. (February 2015) - Jayawardena, A.V.; Meegahapola, L.G.; Robinson, D.A.; Perera, S.
Abstract: The microgrid paradigm has gained much interest in the electricity industry due to the increased penetration of distributed resources. A grid-tied microgrid can be viewed as a single generating entity or a load depending on its power export and import at the grid supply point. Similar to conventional generators, grid-tied microgrids have the potential to be able to participate in the energy market in the future to achieve technical, financial and environmental benefits. Effective participation in the energy markets requires numerous planning tools and a comprehensive understanding of the full capability of the microgrid. This paper presents a systematic approach for developing a capability diagram for a grid-tied microgrid which represents the active and reactive power exchange capability of the microgrid with the main grid. Capability diagrams have been developed for two different microgrids and the impacts of different modelling aspects and network conditions have been analysed using several case studies. Effects of plug-in hybrid electric vehicles, capacitor banks, and other storage devices on microgrid capability diagram have also been addressed in this paper. Furthermore, operating points of the capability diagram have been verified using time domain simulations. Highlights: Developed an optimisation model to derive capability charts for grid-tied microgrid. Capability diagrams have been developed for two different microgrid models. Capability charts can be used as planning and operation tool for grid-tied microgrids. It is vital to model correct DG capability and loads for accurate capability charts. Practical aspects of the implementation of microgrid capability charts were discussed.